HUBUNGAN LANGSUNG DAN TIDAK LANGSUNG ANTARA PARTISIPASI ANGGARAN DAN KINERJA MANAJERIAL MELALUI KOMITMEN ORGANISASI PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Anisza Hasmawati; Sugiyarti Fatma Laela (Institute for Research and Community Empowerment (LPPM TAZKIA), 2011)
mediate the relationship between budgetary participation and managerial performance (indirect relationships), and examines the existence of code of ethics as control variable both in direct and indirect relstionship between budgetary participation and managerial performance in Indonesian Sharia Banking Industry. A path analysis is used to examine the direct and indirect effects of budgetary participation on managerial performance. There is a direct relationship between budgetary participation and managerial performance, but not supported code of ethics as control variable. Budgetary participation affects organizational commitment. There is no relationship between organizational commitment and managerial performance so indirect relationship between budgetary participation and managerial perfomance through organizational commitment is not supported. This research only involved one moderating variable, organizational commitment, when other researchs could bring another moderating variables to examine indirect relationship between budgetary participation and managerial performance. Budgetary participation improves managerial performance in Indonesia Sharia Banking directly as a consequence of management involvement in the budgetary processJEL Classification : M41, C19Keywords : Budgetary participative, managerial performance, code of ethics, organizational commitment, Path Analysis